Pola Komunikasi Suami Istri Perspektif Hadis - Delianti, Putri Aisyah (el-Sunnah: Jurnal Kajian Hadis dan Integrasi Ilmu, 2023)
This article discusses the hadith related to the communication relationship between husband and wife. Qualitative research was conducted through literature study. The method used is the syarah hadith method. Several hadiths are described to find out how the communication was carried out by the Prophet Muhammad Saw. The results and discussion include the notion of communication, communication patterns, hadith editors regarding husband-wife communication, and communication according to the opinion of scholars. This study concludes that the role of communication in a household is the key to a harmonious household. Families that are built on communication will produce families who understand each other.